Islam in Aru, Indonesia: Oral traditions and Islamisation processes from the early modern period to the present. Issue 138 (4th May 2019) - Wellfelt, Emilie; Djonler, Sonny A.
ABSTRACT: The coming of Islam in eastern Indonesia is generally assigned to the activities of Muslim traders from the late 15th century onwards. This assumption is an over-simplification, especially in areas outside the main trade centres. In the Aru islands, Islam was introduced by the mid 17th century. We argue that Islamisation in Aru was initially a matter of internal considerations, rather than trade. We present oral traditions about the expansion of Islam as seen from two locations: Ujir, the historical Muslim centre in Aru on the west coast, and Benjuring, a former stronghold of local ancestral beliefs in the east. The oral sources are juxtaposed with European accounts of the 17th century when Muslim and Protestant centres first developed in Aru. The coming of Islam forced people to either convert or leave for non-Muslim areas. By late colonial times (early 20th century), both Islam and the Protestant church had reached remote villages. The most recent wave of conversions in Aru to state-approved world religions took place in the 1970s. In the last 30 years, the population in Aru has grown, especially in the regency capital Dobo. While Muslims used to be a small minority in Aru with their main centre on Ujir island, the point of gravity has shifted to Dobo, a fast-growing town with a large influx of mostly Muslims from other parts of Indonesia. Islamisation is still ongoing in Aru and the character of Islam is changing.